Improving students' English speaking skills through short videos - Norasiah, Norasiah; Ariesinta, Dimiar; Ardlillah, Queen Fiqi; Jamilah, Jamilah; Ashadi, Ashadi (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2022)
This study aims to improve the English speaking skills of eighth-grade students of MTs Al Falaah Pandak using short videos to aid the learning process in which English is taught as a foreign language. The research was classroom action research with the subjects consisting of 30 eighth graders of MTs Al Falaah Pandak. This research utilized both the qualitative and quantitative data analysis. The qualitative approach to collecting the data was done through observations and interviews with the observation checklist and interview guidelines carefully designed as the instruments. The quantitative approach was done through a survey with questionnaires, field notes and tests as the instruments. The results indicated that using short videos as input in the teaching and learning of speaking can improve the students' speaking skills, as shown by the students' test results that improved gradually from cycle 1 to cycle 2. In cycle 1, the average score of the students' speaking test was 65.8. This noticeably improved in cycle 2, where the average score was 75, showing an improvement by 9.2 points. Further implications and potential implementation of using short videos as input in the teaching and learning of speaking in EFL classes are discussed.